Addressing issues of race, ethnicity and culture in CBT to support therapists and service managers to deliver culturally competent therapy and reduce inequalities in mental health provision for BAME service users. (2019) - Naz, Saiqa; Gregory, Romilly; Bahu, Meera
Abstract: Conversations around improving access to psychological therapies for BAME (Black, Asian and minority ethnic) service users have been ongoing for many years without any conclusion or resolution. BAME service users are often under-represented in primary care mental health services, and often have worse outcomes, leading to them being portrayed as 'hard to reach', and to deterioration in their mental health. They are over-represented in secondary care mental health services. The authors of this article argue that more resources are required in order to understand the barriers to accessing mental health services, and improve both access and recovery for BAME service users. This paper examines concepts such as race, ethnicity and culture. It aims to support service managers and therapists to develop their confidence to address these issues in order to deliver culturally competent psychological therapies to service users from BAME communities, with a focus on primary care. It is based on our experiences of working with BAME communities and the feedback from our training events on developing cultural competence for CBT therapists. The paper also discusses the current political climate and the impact it may have on service users and the need for therapists to take the wider political context into consideration when working with BAME service users. Finally, the paper stresses the importance of addressing structural inequalities at a service level, and developing stronger ethical guidelines in the area of working with diversity for CBT therapists in the UK. Key learning aims: (1) To examine concepts such as race, ethnicity and culture and to provide a shared understanding of these terms for CBT therapists. (2) To assist CBT therapists and supervisors to develop their confidence in addressing issues of race, ethnicity and culture with BAME service users within the current political climate and to deliver culturally competent therapy. (3) To assist service managers to promote equality of access and of outcomes for service users from BAME communities. (4) To understand how unequal expectations of therapists in services impacts on CBT therapists from BAME communities. (5) To widen understanding of some of the structural inequalities at service level which the CBT community needs to overcome, including recommending stronger ethical guidelines around working with diversity in the UK.